Evaluating the effectiveness of projects on the use of alternative energy sources - Sailaubekov, N. T.; Abdygapparova, S. B.; Baytanaeva, B. A.; Shayhutdinova, A. K. (Journal of Economic Research & Business Administration, 2015)
In this paper we propose a method of evaluation of financial and economic efficiency (significance) for the object of alternative energy. The calculated economic and financial indicators allow us to give the most complete picture of the economic reasonability of alternative energy. The methodology used is based on the following stages: initial data collection, calculation of cash flows and the indicators of efficiency and financial feasibility of the project, analysis of the results. The proposed system of criteria takes into account the costs of establishing production bases of energy and allow to evaluate the cost-effectiveness of alternative energy sources. Article addresses the problem of choosing the most efficient type of energy source on the basis of an alternative energy source for the solution of which requires the development of a specific methodology for evaluating the effectiveness of the analyzed species of energy carrier